2014
DOI: 10.1002/nme.4649
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 2‒D bimodular materials and wrinkled membranes based on the parametric variational principle and co‒rotational approach

Abstract: SUMMARYIn the numerical analysis of 2‒D bimodular materials, strain discontinuity is problematic, and the traditional iterative algorithm is frequently unstable. This paper develops a stable algorithm for the large‒displacement and small‒strain analyses of 2‒D bimodular materials and structures. Geometrically nonlinear formulations are based on the co‒rotational approach. Using the parametric variational principle (PVP), a unified constitutive equation is created to resolve the problem induced by strain discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the slack state, both the in-plane principal stresses vanish. 14 Figure 3 gives the membrane stress states.
Figure 3.Membrane stress states.
…”
Section: Analysis Of Wrinklingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the slack state, both the in-plane principal stresses vanish. 14 Figure 3 gives the membrane stress states.
Figure 3.Membrane stress states.
…”
Section: Analysis Of Wrinklingmentioning
confidence: 99%
“…The wavenumber Q is predicted by the analytic formula (14). The total energy of the membrane is obtained by…”
Section: Finite Element Discretizationmentioning
confidence: 99%
“…Jenkins and Leonard [4] proposed a membrane model by introducing a relaxed energy density. Stein developed the viable Poisson's ratio method [5], which is extended by Ding and Yang [6] and Zhang et al [7]. A viable Poisson's ratio and a viable Young's modulus are introduced to modify the constitutive relation.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of analyzing the stress fields of membrane structures have been proposed; Wong and Pellegrino 4,5 studied the in-plane stress field in a square membrane with discrete forces applied on the membrane vertices and found that the stress field comprises identical corner regions under purely radial stress and a central region under uniform biaxial stress, with wrinkles appearing within the uniaxial stress regions. Zhang and colleagues 6,7 proposed a membrane model with viable Young’s modulus and Poisson’s ratio, and then adopted parametric finite element discretization and a smoothing Newton method to obtain a numerical solution. The finite element method 8,9 has been widely adopted; however, its use readily leads to divergent results.…”
Section: Introductionmentioning
confidence: 99%